1998
DOI: 10.1038/bjc.1998.289
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of lactic acid to acidification of tumours: studies of variant cells lacking lactate dehydrogenase

Abstract: Summary Solid tumours develop an acidic extracellular environment with high concentration of lactic acid, and lactic acid produced by glycolysis has been assumed to be the major cause of tumour acidity. Experiments using lactate dehydrogenase (LDH)-deficient rastransfected Chinese hamster ovarian cells have been undertaken to address directly the hypothesis that lactic acid production is responsible for tumour acidification. The variant cells produce negligible quantities of lactic acid and consume minimal amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(133 citation statements)
references
References 16 publications
7
119
0
3
Order By: Relevance
“…Increased activity of LDH, being linked with intratumoral hypoxia and acidity (Yamagata et al, 1998), should be related with aggressive tumour features as shown in a previous study on CA9 in NSCLC . As HIFas regulate glycolysis and LDH transcription, we further assessed the HIF association with LDH expression.…”
supporting
confidence: 52%
“…Increased activity of LDH, being linked with intratumoral hypoxia and acidity (Yamagata et al, 1998), should be related with aggressive tumour features as shown in a previous study on CA9 in NSCLC . As HIFas regulate glycolysis and LDH transcription, we further assessed the HIF association with LDH expression.…”
supporting
confidence: 52%
“…Acidification of the extracellular matrix in the tumor is therefore expected either as a result of carbonic acid or lactate release from cancer cells. (28,29) The pH in the tumor vein was significantly lower than that of the tumor artery. All nine cases with CA9 and/or LDH-5 overexpression had very low pH values in the tumor vein, supporting the concept that these enzymes are responsible for the acidic conditions prevailing in the tumor ambient.…”
Section: Discussionmentioning
confidence: 95%
“…This increase in the intracellular pH is concomitant with an increment of DNA synthesis (8,13,14), cell cycle progression (15)(16)(17), serum and substrate-independent growth (8) and the in vivo growth of the tumor (8,18) and all these phenomena trigger a pathological and disorganized increase in density and cell number. However, tumors are able to create an acidic environment even in conditions of reduced production of lactate, suggesting that the aerobic metabolism is not the major mechanism responsible for the development of an acidic microenvironment within solid tumors such as oral squamous cell carcinoma (OSCC) (19,20). On the one hand, the same favourable conditions are maintained for the tumor cells, and on the other hand the selection of highly malignant cancer cells (which can survive in a hostile environment) is facilitated (21).…”
Section: Introductionmentioning
confidence: 99%